Psychiatric Disorders in Young Adult Intercountry Adoptees: An Epidemiological Study - Tieman, Wendy; van der Ende, Jan; Verhulst, Frank C. (The American journal of psychiatry, 2005)
OBJECTIVE: The prevalences of psychiatric disorders in young adult intercountry adoptees and nonadopted young adults from the general population were compared. METHOD: In the Netherlands, a total of 1,484 young adult intercountry adoptees (72.5% of the original sample at age 10-15 years) and 695 nonadopted subjects (78.1% of the original sample) of comparable age from the general population were interviewed by using a standardized psychiatric interview generating DSM-IV diagnoses. RESULTS: The adopted young adults were 1.52 times as likely to meet the criteria for an anxiety disorder as the nonadopted young adults; the 95% confidence interval (CI) was 1.15-2.00. The adoptees were 2.05 (95% CI=1.32-3.17) times as likely to meet the criteria for substance abuse or dependence. The adopted men were 3.76 (95% CI=1.69-8.37) times as likely to have a mood disorder as nonadopted men, while for women there was no significant difference between adoptees and nonadoptees. No significant difference for the diagnosis of disruptive disorder was found. For all diagnoses together, adoptees with low and middle parental socioeconomic status in childhood did not differ from the comparison subjects, while adoptees with high parental socioeconomic status were 2.17 times (95% CI=1.50-3.13) as likely to meet the criteria for a disorder as nonadoptees with high parental socioeconomic status. CONCLUSIONS: Intercountry adoptees run a higher risk of having severe mental health problems in adulthood than nonadoptees of the same age. The risk of later malfunctioning differs for different disorders and different groups of adoptees.